2014
DOI: 10.1111/wrr.12234
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombin as important factor for cutaneous wound healing: Comparison of fibrin biomatrices in vitro and in a rat excisional wound healing model

Abstract: Fibrin biomatrices have been used for many years for hemostasis and sealing and are a well-established surgical tool. The objective of the present study was to compare two commercially available fibrin biomatrices regarding the effect of their thrombin concentration on keratinocytes and wound healing in vitro and in vivo. Keratinocytes showed significant differences in adhesion, viability, and morphology in the presence of the fibrin matrices in vitro. A high thrombin concentration (800-1,200 IU/mL) caused det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Additionally, all-allogeneic and all-autologous sealants provide mechanically similar graft adhesion to articular cartilage, and therefore the biological ramifications could be considered when deciding which source to use. Autologous components contain lower fibrinogen and thrombin concentrations compared to allogeneic sources, and this could lead to improved cell migration and matrix deposition[4650]. Our results demonstrate that the benefits of autologous source components can be appreciated without sacrificing mechanical performance of the fibrin sealant.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, all-allogeneic and all-autologous sealants provide mechanically similar graft adhesion to articular cartilage, and therefore the biological ramifications could be considered when deciding which source to use. Autologous components contain lower fibrinogen and thrombin concentrations compared to allogeneic sources, and this could lead to improved cell migration and matrix deposition[4650]. Our results demonstrate that the benefits of autologous source components can be appreciated without sacrificing mechanical performance of the fibrin sealant.…”
Section: Discussionmentioning
confidence: 90%
“…On contrary, in their in vitro model of wound reepithelialization, Geer and colleagues [ 43 ] showed that fibrin affects keratinocyte activation and increases the consistency of the healing response. An interpretation to such discrepancy may largely depend on the composition of fibrin biomatrices that might considerably control its effect on wound healing [ 44 ]. Additionally, the efficacy of fibrin sealant depends greatly on the surgical situation it is used in [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are also widely used for tissue engineering, and drug and cell delivery. However, studies on using purified fibrin sealant alone to enhance wound healing are limited [ [51] , [52] , [53] , [54] ]. The outcomes are positive but inconsistent and limited.…”
Section: Introductionmentioning
confidence: 99%